Editorial - Fernández-Arata, Manuel (2023)
We are pleased to announce the publication of Volume No. 29 of Liberabit, Peruvian Journal of Psychology. This volume features seven articles, as described in what follows. First, Ricardo Jorquera-Gutiérrez and Felipe Guerra-Diaz report on a psychometric analysis of the Perceived Stress Scale in its two versions, 14- and 10-item (PPS-14 and PSS-10), carried out with Chilean teachers. Through a robust maximum likelihood (MLR) method, the evidence supports a model of two related factors, shows good reliability of the factors in both versions of the instrument, and demonstrates invariance of the two-factor structure for men and women in the two versions. Florencia Stelzer, Yésica Aydmune, Ana García-Coni, Santiago Vernucci, and Isabel Introzzi analyze cognitive and attitudinal factors involved in the prediction of mathematics performance in Argentine high school students. Their article reports that perceived competence, enjoyment for mathematics, and working memory are significant predictors of a large percentage of performance in mathematics in the first year of secondary school, controlling for the effect of prior knowledge and school year.